Identification of an algal xylan synthase indicates that there is functional orthology between algal and plant cell wall biosynthesis. Issue 3 (20th February 2018) - Jensen, Jacob Krüger; Busse‐Wicher, Marta; Poulsen, Christian Peter; Fangel, Jonatan Ulrik; Smith, Peter James; Yang, Jeong‐Yeh; Peña, Maria‐Jesus; Dinesen, Malene Hessellund; Martens, Helle Juel; Melkonian, Michael; Wong, Gane Ka‐Shu; Moremen, Kelley W.; et al.
Summary: Insights into the evolution of plant cell walls have important implications for comprehending these diverse and abundant biological structures. In order to understand the evolving structure–function relationships of the plant cell wall, it is imperative to trace the origin of its different components. The present study is focused on plant 1, 4‐β‐xylan, tracing its evolutionary origin by genome and transcriptome mining followed by phylogenetic analysis, utilizing a large selection of plants and algae. It substantiates the findings by heterologous expression and biochemical characterization of a charophyte alga xylan synthase. Of the 12 known gene classes involved in 1, 4‐β‐xylan formation, XYS1/IRX10 in plants, IRX7, IRX8, IRX9, IRX14 and GUX occurred for the first time in charophyte algae. An XYS1/IRX10 ortholog from Klebsormidium flaccidum, designated K. flaccidum XYLAN SYNTHASE‐1 ( Kf XYS1), possesses 1, 4‐β‐xylan synthase activity, and 1, 4‐β‐xylan occurs in the K. flaccidum cell wall. These data suggest that plant 1, 4‐β‐xylan originated in charophytes and shed light on the origin of one of the key cell wall innovations to occur in charophyte algae, facilitating terrestrialization and emergence of polysaccharide‐based plant cell walls.